1993
DOI: 10.1080/00207549308956884
|View full text |Cite
|
Sign up to set email alerts
|

A construction algorithm for the machine layout problem with fixed pick-up and drop-off points

Abstract: A construction algorithm which considers some practical aspects of the machine layout problem is presented. The methodology considers machine dimensions and their input and output locations with flow data. The layout is generated on a continuum, considering the best configuration and orientation of input and output locations of machines to minimize the material flow cost. The location procedure searches along the boundary of existing machines. A bi-criterion optimization approach is proposed to overcome one of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…The problem set 1 is used for conducting these preliminary experiments. It consists of four test problem instances of 6 and 12 departments (Welgama and Gibson 1993), 7 departments (Wu and Appleton 2002) and 20 departments (Aiello et al 2002). In addition, to justify the proposed approach, it is compared with the hybrid GA based random search approach that use SA for local search (Deb and Bhattacharyya 2005).…”
Section: Methodsmentioning
confidence: 99%
“…The problem set 1 is used for conducting these preliminary experiments. It consists of four test problem instances of 6 and 12 departments (Welgama and Gibson 1993), 7 departments (Wu and Appleton 2002) and 20 departments (Aiello et al 2002). In addition, to justify the proposed approach, it is compared with the hybrid GA based random search approach that use SA for local search (Deb and Bhattacharyya 2005).…”
Section: Methodsmentioning
confidence: 99%
“…It is to be noted that the analytic steepest descent for layout improvement has been employed in past Mir, 1990). In addition, the heuristic cluster boundary search using a corner search has also been reported (Ahmad, 2006;Welgama, 1993). However, little research can be found on synergistically employing the two techniques in one algorithm, a venue that offers significant promise.…”
Section: Introductionmentioning
confidence: 99%
“…This heuristic search reduces the otherwise infinite solution space to tractable limits. Since our placement decisions are restricted only to the corners of placed modules, for a given module, there are only O(n) possible locations supporting the use of some fast pseudo-exhaustive search in a hierarchical manner (Ahmad, 2006;Welgama, 1993;.…”
Section: Proposed Algorithmmentioning
confidence: 99%
“…It is to be noted that the analytical steepest descent for layout improvement has been employed in the past [19,20]. In addition, the heuristic cluster boundary search using a corner search has also been reported [1,2,21]. However, little research can be found on synergistically employing the two techniques in the same algorithm -an option that offers significant promise.…”
Section: Introductionmentioning
confidence: 99%